How wages change: Micro evidence from the International Wage Flexibility Project - William T. Dickens; Lorenz Goette; Erica L. Groshen; Steinar Holden; Julian Messina; Mark E. Schweitzer; Jarkko Turunen; Melanie E. Ward (Federal Reserve Bank of New York, 2007)
How do the complex institutions involved in wage setting affect wage changes? The International Wage Flexibility Project provides new microeconomic evidence on how wages change for continuing workers. We analyze individuals' earnings in thirty-one different data sets from sixteen countries, from which we obtain a total of 360 wage change distributions. We find a remarkable amount of variation in wage changes across workers. Wage changes have a notably non-normal distribution; they are tightly clustered around the median and also have many extreme values. Furthermore, nearly all countries show asymmetry in their wage distributions below the median. Indeed, we find evidence of both downward nominal and real wage rigidities. We also find that the extent of both these rigidities varies substantially across countries. Our results suggest that variations in the extent of union presence in wage bargaining play a role in explaining differing degrees of rigidities among countries.
Keywords: E3; J3; J5; 330; wage setting; wage change distributions; downward nominal wage rigidity; downward real wage rigidity; Lohnrigidität; Lohnpolitik; EU-Staaten; Norwegen; Schweiz; USA